A leader's legacy Tun Abdul Razak - Ong, Justin; Teoh, Lina, production; Hale, Chris; Dostellas (Firm); Perbadanan Kemajuan Filem Nasional Malaysia ([Kuala Lumpur] : National Film Development Corporation Malaysia (FINAS) and NGC Network Asia, 2010)
For the first time, National Geographic Channel's exclusive access takes you behind the scenes to reveal the personal story of the inspirational second Prime Minister of Malaysia, Tun Abdul Razak, fondly known as the'Father of Development'. His pioneering spirit paved the way for the rise of modern Malaysia.
Narrator, Harry Chase
Editor, Eva E. Zahar
dvd format
Keywords: Abdul Razak bin Dato' Hussein, -- Tun, -- 1922-1976; Prime ministers -- Malaysia; Malaysia -- History; Malaysia -- Politics and governments; Malaysia -- Social life and customs; Malaysia -- Civilization